Caught up or Protected by the Past? How Reputational Histories Matter for Agencies' Media Reputations. (2nd February 2021) - Salomonsen, Heidi Houlberg; Boye, Stefan; Boon, Jan
Abstract: Reputation scholars have convincingly demonstrated the relevance of understanding the behavior of government agencies as motivated by reputational concerns. Yet we must still expand our understanding of how agency audiences pass reputational judgments. Combining insights from bureaucratic reputation theory with psychological theories (motivated reasoning and attribution theory), this article theorizes and tests whether agencies' reputational histories increase the likelihood of receiving positive or negative newspaper coverage. Our findings are based on an extensive coding of 11, 041 newspaper articles over a 10-year period in Denmark and Flanders (Belgium) regarding 40 agencies. We introduce a measure of reputational history from communication studies. The analysis identifies that both negative and positive reputational histories are related to the valence of newspaper coverage, suggesting that the past reputations of agencies are part of the cognitive basis upon which audiences form reputational judgment.